Dynamic psychophysiological correlates of a learning from text episode in relation to reading goals. (April 2018) - Scrimin, Sara; Patron, Elisabetta; Ruli, Erlis; Pagui, Clovis Euloge Kenne; Altoè, Gianmarco; Mason, Lucia
Abstract: This study aimed to investigate undergraduates' cardiac activity during an episode of complex learning from text. Specifically, we examined (a) heart rate (HR) and (b) heart rate variability (HRV) as psychophysiological measures while students read a science text and were tested on it. Reading goals were also taken into account: Students were asked to read for themselves to know more on a topic, or to read to perform well to gain course credit. Undergraduates (N = 50) were randomly assigned to one of the two reading goal conditions. Their HR and HRV were registered at baseline, while reading the text, during the testing phase, and while recovering from the task. Findings confirmed that in the condition with the reading goal focused on good performance, the students comprehended the text better than the students who read for themselves. Two mixed-effects models examined HR and HRV trends during the four phases of the learning episode. Findings showed a general trend in which students' HRV was greater in the reading phase compared to baseline. HR decreased during reading and increased during the testing phase. This pattern indicates a deep cognitive effort of students while reading that gave way to higher psychophysiological arousal in the testing phase. Moreover, a series of linear regression models revealed that being under aroused and in a state of receptive calm during the reading phase allowed greater performance. Educational implications are drawn. Highlights: Cardiac activity varies during a learning from text episode. HR decreases while reading and increases during testing. HRV, an index of parasympathetic activity, increases while reading. A state of under arousal and receptive calm while reading allows a better performance.